Spring-Assisted Strip Craniectomy Versus Cranial Vault Remodeling: Long-Term Psychological, Behavioral, and Executive Function Outcomes. Issue 7 (October 2020) - Chandler, Ludmila; Allam, Omar; Park, Kitae E.; Smetona, John; Gabrick, Kyle S.; Wu, Robin T.; Morgan, Chelsea; Park, Sydney E.; Chapman, Leah A.; Couture, Daniel E.; David, Lisa R.; Runyan, Christopher M.; et al.
Abstract : Background: Controversy exists regarding the optimal surgical approach for non-syndromic sagittal synostosis. This study provides the first comparative analysis of the long-term behavioral, psychological, and executive function outcomes for patients who underwent either cranial vault remodeling (CVR) or spring-assisted strip craniectomy (SAS). Methods: Thirty-six CVR patients and 39 SAS patients were evaluated. Parents and caregivers completed the Behavior Rating Inventory of Executive Function (BRIEF) and the Behavior Assessment System for Children, Second Edition (BASC-2) to evaluate behavioral, emotional, social, adaptive, and executive functioning skills. Results: There were no statistically significant differences between the CVR and the SAS groups ( P  > 0.05) in any of the BRIEF areas of function. Furthermore, the BASC-2 battery illustrated no significant differences in all areas analyzed except one. Among the 2 groups, the CVR group was rated as having fewer social withdrawal symptoms on the BASC-2 (47.00 ± 10.27) compared to the SAS cohort (54.64 ± 10.96), F  = 6.79, P  = 0.012, Cohen d  = 0.688. However, both means were still within the normal range. Conclusions: Children undergoing SAS and CVR procedures for isolated sagittal synostosis were not rated as having clinically significant behavioral, emotional, social, adaptive, or executive functioning problems on parental forms. Abstract : Supplemental Digital Content is available in the text